Metaphor and Persuasion in Arabic Da'wah Discourse: A Cognitive Linguistic Approach - Moh. Nadhif; Imam Athoir Rokhman; Moh. Subthi Buchori; Rifqi Abqoriya; Rodifatul Chasanah (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2026)
This study examines metaphor as a persuasive cognitive mechanism in contemporary Arabic da'wah discourse, focusing on digital khutbah delivered through online platforms. Unlike previous studies that primarily rely on classical rhetorical analysis (balāghah), this research adopts a cognitive linguistic perspective to explore how metaphor structures religious meaning and influences audience interpretation. Drawing on Conceptual Metaphor Theory the study analyzes a corpus of 30 khutbah texts collected from YouTube and official religious platforms published between 2020 and 2025. Data were examined using the Metaphor Identification Procedure (MIP) to identify conceptual metaphors and analyze their persuasive functions. The findings indicate that dominant metaphors such as الإيمان نور (faith is light), الذنوب مرض (sin is disease), and الحياة رحلة (life is a journey) play a significant role in framing religious understanding, evoking emotional engagement, and guiding moral behavior. This study contributes to cognitive linguistics and discourse analysis by providing an empirical and contemporary account of metaphor in Arabic da'wah discourse, demonstrating that metaphor functions not only as a rhetorical device but as a cognitive and persuasive strategy in digital religious communication.